A DFT study of spherands containing five anisyl groups - Highly preorganized to bind the alkali metal - Elroby, Shabaan A. K.; Lee, Kyu Hwan; Cho, Seung Joo; Hinchliffe, Alan (NATL RESEARCH COUNCIL CANADA-N R C RESEARCH PRESS, 2006)
Although anisyl units are basically poor ligands for metal ions, the rigid placements of their oxygens during synthesis rather than during complexation are undoubtedly responsible for the enhanced binding and selectivity of the spherand. We used standard B3LYP/6-31G** (5d) density functional theory (DFT) to investigate the complexation between spherands containing five anisyl groups, with CH2-O-CH2 (2) and CH2-S-CH2 (3) units in an 18-membered macrocyclic ring, and the cationic guests (Li+, Na+, and K+). Our geometric structure results for spherands 1, 2, and 3 are in good agreement with the previously reported X-ray diffraction data. The absolute values of the binding energy of all the spherands are inversely proportional to the ionic radius of the guests. The results, taken as a whole, show that replacement of one anisyl group by CH2-O-CH2 (2) and CH2-S-CH2 (3) makes the cavity bigger and less preorganized. In addition, both the binding and specificity decrease for small ions. The spherands 2 and 3 appear beautifully preorganized to bind all guests, so it is not surprising that their binding energies are close to the parent spherand 1. Interestingly, there is a clear linear relation between the radius of the cavity and the binding energy (R-2 = 0.999).
Keywords: COMPLEXATION